Compliance Costs, Access to Finance and Financial Performance of Dairy Farming in Uganda - Nicholas Akampurira (Uganda Christian University, 2023)
The intention of the study was toidentifythe compliance costs, access to finance and financial performance in dairy farming Gomba district as the case study. And this study was done under the three objectives,to determine the level of financial performance of dairy farmers dairy in Gomba District, the relationship between compliance cost and financial performance of dairy farmers, the relationship between access to finance and financial performance of dairy farming in Uganda. Collection data of was conducted through the use of a questionnaire and interview guide, and during data collection purposive sampling method was followed, the researcher used both qualitative and quantitative methods were used to analyze and interplete data as a sample size of 49 respondents was used. In the recamp of the study, the following were identified, Since access to finance is not the main determinant of improved financial performance, the study suggests that farmers and dairy managers to always make rational decisions and proper planning in order for available finances to yield more returns. Encouraged to spot milk breeds of cattle forexample fresians and jessy cows, which produce large volumes of milk hence more milk produced in all seasons generate more income for dairy farming hence improving in financial performance of dairy sector. The study advises farmers to have loans from trusted financial institutions at low interest rates for financing their dairy sectors in order to meet their obligations in time hence being cost effective to dairy farmers. Farmers are encouraged to enhance their milk standards as they also maximize milk production, encourages farmers to adopt commercial dairy farming, encourages farmers to adopt capital and labour intensive techniques of production, encourages farmers always to keep records of their dairy farms, dairy farmers and processors should have a strong track record, working to be economically viable while improving the health of the environment, workforce and the broader community and also suggested other areas of research.
This is a dissertation.